Upaya Meningkatkatan Hasil Belajar Peserta Didik Kelas II SDN 2 Batu Buil dalam Pembelajaran Pak Melalui Model Pembelajaran Problem Based Learning (PBL) - Ernawati Ernawati (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to improve learning outcomes for Catholic Religious Education and Character through the Problem Based Learning (PBL) method in class 2 of SDN 2 BatuBuil in the 2024/2025 academic year. The type of research is Classroom Action Research (PTK) which is carried out in two cycles, each consisting of planning, implementation, observation and reflection. The material discussed is "God Gave Me a Family" with a focus on activities and positive attitudes towards family. The research subjects were 8 grade 2 students. Data was collected through observation and tests. The results show an increase in learning outcomes from cycle I to cycle II, with significant changes in the affective aspect. In cycle I, only 2 students were proficient, while in cycle II this increased to 4 students. The post-test results also showed improvement: in cycle I, 3 students were in the undeveloped category, while in cycle II there were no students in that category, with 5 students reaching the advanced category. The application of PBL has proven to be effective in increasing students' understanding and skills in applying the values ​​taught.